Neonatal Enterovirus-Associated Myocarditis in Dizygotic Twins: Myocardial Longitudinal Strain Pattern Analysis - Stefania Giampetruzzi; Domenico Sirico; Nicoletta Mainini; Marta Meneghelli; Enrico Valerio; Sabrina Salvadori; Giovanni Di Salvo (MDPI AG, 2024)
Enteroviruses (EVs) are the most common causes of viral myocarditis in neonates. Neonatal enterovirus myocarditis manifestations range from nonspecific febrile illness to congestive heart failure and cardiogenic shock with high risk of in-hospital mortality and long-term cardiac sequelae. Early recognition is essential to undertake appropriate therapy and predict outcomes. Echocardiography and echo-derived left ventricular strain measures seem promising for these purposes. We herein report two cases of neonatal enterovirus-associated myocarditis in dichorionic diamniotic twins, with different presentation, clinical course, and intensity of treatments.